Splat the Cat - Scotton, Rob. (New York : HarperCollinsPublishers, 2008)
Splat the Cat is nervous about his first day at cat school, but once he arrives he realizes he had nothing to worry about.
Pub Weekly
School Library Journal
Wilson's Children
Booklist, July 2008
Bulletin (Center for Children's books), July 2008
Horn Book, April 2009
Keywords: Cats -- Juvenile fiction; First day of school -- Juvenile fiction; Schools -- Juvenile fiction; Cats -- Fiction; First day of school -- Fiction; Schools -- Fiction; Cats -- Fiction; First day of school -- Fiction; School stories